(untitled) (World Journal of Current Medical and Pharmaceutical Research, 2026)
Background: Sepsis and septic shock are major causes of morbidity and mortality in intensive care units. Early prognostic markers are essential for risk stratification. The neutrophil-lymphocyte ratio (NLR), derived from a routine complete blood count, is a simple and inexpensive marker of systemic inflammation. Objectives: To assess the relationship between NLR and mortality in patients with sepsis and septic shock and to determine an NLR cut-off associated with unfavourable outcomes. Methods: A prospective observational study was conducted among 170 patients admitted to the Medical and Respiratory Intensive Care Units at Basaveshwara Medical College and Hospital, Chitradurga, from August 2022 to February 2024. Admission NLR was calculated and patients were categorized into NLR <3 and NLR >3 groups. Clinical, biochemical, and outcome parameters were compared using Chi-square and independent-sample t-tests, with p<0.05 considered significant. Results: Of 170 patients, 114 (67.1%) had NLR <3 and 56 (32.9%) had NLR >3. Significant differences were observed in ESR (32.8 vs 37.2, p=0.021), bilirubin (4.1 vs 2.5 mg/dL, p<0.001), creatinine (3.5 vs 2.2 mg/dL, p<0.001), mean arterial pressure (106.7 vs 86.7 mmHg, p<0.001), total leucocyte count, and 24-hour NLR (1.66 vs 5.0, p<0.001). Mortality was comparable between groups (12.3% vs 12.5%, p=0.967). Conclusion: NLR correlated with several markers of organ dysfunction and disease severity but did not discriminate in-hospital mortality in this cohort. Larger multicentric studies with serial NLR measurements are warranted.